Cardiovascular adverse effects of immunotherapy in cancer: insights and implications - Du, Haiping; Wang, Jie; Wang, Zhen (Frontiers in Oncology, 2025)
Immunotherapy has revolutionized cancer treatment, offering novel therapeutic strategies such as immune checkpoint inhibitors (ICIs), chimeric antigen receptor (CAR) T-cell therapy, and cancer vaccines. However, these modalities are associated with varying cardiovascular toxicities that may affect treatment continuation and patient outcomes. Cardiovascular complications from ICIs, such as myocarditis (incidence 0.04–1.14%, mortality 25–50%), arrhythmias, heart failure, and thromboembolic events, are primarily mediated by autoreactive T-cell activation and immune-related inflammation. CTLA-4 and PD-1/PD-L1 blockade disrupts immune homeostasis, leading to direct myocardial infiltration and cytokine-mediated damage. Up to 26% of patients receiving CAR T-cell therapy develop cardiovascular events, often secondary to cytokine release syndrome (CRS). Excessive release of pro-inflammatory cytokines (e.g., IL-6, IFN-γ) leads to endothelial dysfunction, hypotension, myocardial depression, arrhythmias, and acute coronary syndromes. Rare cases of myocarditis and arrhythmias have been reported following mRNA vaccine administration, particularly in younger males. Proposed mechanisms include innate immune activation via Toll-like receptors, leading to cytokine release and myocardial inflammation. Dendritic cell vaccines show lower cardiovascular toxicity, likely due to their localized and cell-specific immune activation. This review provides a comprehensive evaluation of cardiovascular adverse events across immunotherapy classes. It underscores the importance of early detection through biomarkers, risk stratification, and multidisciplinary cardio-oncology collaboration. Future research should aim to refine immunotherapy protocols to minimize cardiotoxic risks while preserving anti-tumor efficacy.